2015
DOI: 10.1124/mol.115.098376
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical Evaluation of DMA, a Bisbenzimidazole, as Radioprotector: Toxicity, Pharmacokinetics, and Biodistribution Studies in Balb/c Mice

Abstract: Radiotherapy, a therapeutic modality of cancer treatment, nonselectively damages normal tissues as well as tumor tissues. The search is ongoing for therapeutic agents that selectively reduce radiation-induced normal tissue injury without reducing tumoricidal effect, thereby increasing the therapeutic ratio of radiation therapy. Our laboratory established 5-(4-methylpiperazin-1-yl)-2-[2ʹ-(3,4-dimethoxyphenyl)-59benzimidazolyl] benzimidazole (DMA) as noncytotoxic radioprotector in mammalian cells. DMA showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…V ss (0.84 L/kg) of CSA was substantially greater than the total blood volume (approximately 0.0312 L/kg) of rats, and t 1/2, λz was relatively long, indicating that CSA had an extensive affinity with the tissues rather than plasma protein and was readily distributed into the extravascular system . This is in agreement with the study of Hua et al, where CSA underwent a rapid and wide distribution in tissues and organs throughout the whole body, especially in the small intestine, liver, and kidneys.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…V ss (0.84 L/kg) of CSA was substantially greater than the total blood volume (approximately 0.0312 L/kg) of rats, and t 1/2, λz was relatively long, indicating that CSA had an extensive affinity with the tissues rather than plasma protein and was readily distributed into the extravascular system . This is in agreement with the study of Hua et al, where CSA underwent a rapid and wide distribution in tissues and organs throughout the whole body, especially in the small intestine, liver, and kidneys.…”
Section: Resultssupporting
confidence: 90%
“…readily distributed into the extravascular system. 26 This is in agreement with the study of Hua et al, 19 where CSA underwent a rapid and wide distribution in tissues and organs throughout the whole body, especially in the small intestine, liver, and kidneys. After oral administration, CSA was absorbed rapidly into the circulation to reach C max (2.77 μM) at approximately 21 min and eliminated slowly with a t 1/2,λz of 12.90 h, CL/F of 3.54 L h −1 kg −1 , and relatively large V d /F of 54.64 L/kg.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 91%
“…H33342 derivatives such as tris (TBZ), and dimethoxty (DMA) benzimidazole were also studied for their radioprotective efficacy in vivo. DMA showed an effective radioprotection in mice at single nontoxic oral dose with a DMF of 1.28 (Nimesh et al 2015). DMA-treated mice showed delayed radiation sickness, such as weight loss, irritability and lethargy.…”
Section: Dna-binding Agentsmentioning
confidence: 99%
“…Further mechanistic study revealed that DMA exhibits radioprotective activity by activating NFκB signaling through NIK/IKK pathway in vitro as well as in vivo . DMA when administered 2 hr prior to 8 Gy whole‐body irradiation showed an impressive rescue of radiation‐induced morbidity, in terms of weight loss and mortality, without a change in tumor response …”
Section: Radioprotective Agents: Translational Advancesmentioning
confidence: 99%